2017
DOI: 10.1016/j.eneco.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A regime-switching copula approach to modeling day-ahead prices in coupled electricity markets

Abstract: The recent price coupling of many European electricity markets has triggered a fundamental change in the interaction of day-ahead prices, challenging additionally the modeling of the joint behavior of prices in interconnected markets. In this paper we propose a regime-switching AR-GARCH copula to model pairs of day-ahead electricity prices in coupled European markets. While capturing key stylized facts empirically substantiated in the literature, this model easily allows us to 1) deviate from the assumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Many studies have used copula models to understand movements across markets (e.g. Ning, 2010;Meng and Liang, 2013;Reboredo & Ugolini, 2015;Kleinow & Moreira, 2016;Lourme & Maurer, 2017;Pircalabu & Benth, 2017;Ji et al, 2018). A copula is a multivariate cumulative distribution function with uniform marginal distributions on the interval (0, 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used copula models to understand movements across markets (e.g. Ning, 2010;Meng and Liang, 2013;Reboredo & Ugolini, 2015;Kleinow & Moreira, 2016;Lourme & Maurer, 2017;Pircalabu & Benth, 2017;Ji et al, 2018). A copula is a multivariate cumulative distribution function with uniform marginal distributions on the interval (0, 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mahringer et al (2015) use a structural approach, where they model the supply and demand in a two-market setup that incorporates market coupling and allows for closed-form solutions for transmission rights. Pircalabu & Benth (2017) propose a reduced-form model in a two-market setup defined in discrete time that includes the market coupling mechanism using a regime-switching model, but no closed-form solutions for derivative prices are given.…”
Section: Introductionmentioning
confidence: 99%
“…As Pircalabu & Benth (2017) we propose a reduced-form model for day-ahead prices in a two-market setup that takes market coupling into account. Compared to Pircalabu & Benth (2017), we differentiate us by formulating the model in continuous time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the model efficiently reflect the asymmetric and heavy tail dependence of financial markets among countries that were considered. Pircalabu and Benth (2017) used a regime-switching copula to model the interdependence of electricity market prices among European countries. The authors identified the existence of the tail dependence of the prices.…”
Section: Introductionmentioning
confidence: 99%